Applied Vegetation Science in 2010: new opportunities for the vegetation scientists - Chiarucci, Alessandro (2010)
Fil: Chiarucci, Alessandro. University of Siena. Department of Environmental Science G. Sarfatti. Biodiversity and Conservation Network; Italia